Higher Education and Sexual Violence: Affirming the Rights of Victims in Indonesian Legal System - Djawie, Muh. Fauzan Anbarha S; Pakan, Vierre Dharma (Law Research Review Quarterly, 2023)
Sexual Violence Crimes are all acts that meet the elements of a criminal act as regulated in this Law and other acts of sexual violence as regulated in the Law as long as it is stipulated in this Law. Sexual violence is one of the crimes of sexual violence that often occurs in Indonesian society and even in the world. Sexual violence does not only occur in the public sphere but often occurs in the family sphere. Where family and home should be the safest shelter, but the bad things actually come from home and family. The purpose of this study is to analyze how the victimization study of the protection for victims of sexual violence that often occurs. From the victim herself, the lack of courage to tell about the sexual violence that has been experienced is one of the obstacles to proceeding the case to the authorities. The feeling of not being brave is also influenced by the community's thinking that victims of sexual violence are a disgrace. In juridical considerations, the judge looks for criminal elements and then looks at the facts at trial, how the victim decides what will happen to the victim and the perpetrator. Psychological trauma to the victim must also be healed even if he is a long-term worker with the help of psychologists and psychiatrists.